PEMBERDAYAAN MASYARAKAT LOKAL DALAM AKTIVITAS PARIWISATA BUDAYA BALI - I Nyoman Murtana (Pascasarjana Institut Seni Indonesia Surakarta, 2008)
In social life, art considerably can help to perfect human and their society in physi- cal, spiritual and psychological side. Â Based on their belief the role and function of art, like mentioned above, resulting many kinds of art which goes to manifestation of artist creativity and their society. Â No exception happens in Bali, too. Â There are lots of various arts which are as the hairs of an old agricultural-feudalism society that people today of Â desperately reborn and developed them.Â Â In case of one of preservation conceptions, it Â is made such as classification of art; sacred art and profane. Â The classification is significantly made to anticipation tourism organizer to not harmfully perform that sacred art to be sold by tourist. Â Unfortunately, this classification has no cultural power to be obeyed, so till today it is consequently still be a conflict. Â What is all about happens due to that tourism such as has a big power to screw up that classifications of sacred art and profane. Â It will be more ridiculous when there is an art work which previously become a sacred art must be sold for the sake tourists satisfaction. Â It seems that tourism activities is identical to market. Bali, actually, is merely the market. Â In â€œsmallâ€ part it goes to art market such as art performance, handy craft, painting, sculpture, and other else, then natural tourism object on the other side.Â Â Based on the facts show that art reproduction only be done by a small society which has skill to create work of arts. Â Meanwhile, the small society has no evenly big chance due to the local government indicated less atten- tion to empowering them. Â Today, there are some people who has desperately kept the Â maintaining the image of Balinese cultural identity by undergoing traditional and religion Â ritual ceremony hugely and attractively, but it comes to unpleasantly that the lesson just to be anjoyed by as a merely profane performance.Â Key words: local society, tourism, empowering.